Production and characterisation of bacterial cellulose hydrogels loaded with curcumin encapsulated in cyclodextrins as wound dressings. (September 2019) - Gupta, A.; Keddie, D.J.; Kannappan, V.; Gibson, H.; Khalil, I.R.; Kowalczuk, M.; Martin, C.; Shuai, X.; Radecka, I.
Graphical abstract: Highlights: Curcumin:cyclodextrin-loaded cellulose based biosynthetic hydrogels were produced. These novel hydrogels exhibited haemocompatibility and cellular biocompatibility. CUR:HPβCD-loaded-bacterial cellulose showed antibacterial and antioxidant properties. Acute and chronic wounds could benefit from their application. Abstract: Natural bioactive materials with wound healing properties such as curcumin are attracting interest due to the emergence of resistant bacterial strains. The hydrophobicity of curcumin has been counteracted by using solubility enhancing cyclodextrins. Hydrogels facilitate wound healing due to unique properties and 3D network structures which allows encapsulation of healing agents. In this study, biosynthetic cellulose produced by Gluconacetobacter xylinus (ATCC 23770) was loaded with water soluble curcumin:hydroxypropyl-β-cyclodextrin supramolecular inclusion complex produced by a solvent evaporation method to synthesise hydrogel dressings. The ratios of solvents to solubilise curcumin and hydroxypropyl-β-cyclodextrin were tested for the production of the inclusion complex with optimum encapsulation efficacy. The results confirmed that hydroxypropyl-β-cyclodextrin enhanced the aqueous solubility of curcumin and allowed loading into bacterial cellulose hydrogels. These hydrogels were characterised for wound management applications and exhibited haemocompatability, cytocompatability, anti-staphylococcal and antioxidant abilities and therefore support the potential use of the curcumin:hydroxypropyl-β-cyclodextrin-loaded-bacterial cellulose as hydrogel dressings.